2020
DOI: 10.1101/2020.07.14.20153858
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Community-level SARS-CoV-2 Seroprevalence Survey in urban slum dwellers of Buenos Aires City, Argentina: a participatory research

Abstract: Background By July 1st, the incidence rate of RT-qPCR SARS-CoV-2 infection was 5.9% in Barrio Padre Mugica, one of the largest slums in Buenos Aires City. This study aimed to establish the seroprevalence of SARS-CoV-2 three months after the first case was reported. Methods Between June 10th and July 1st, a cross-sectional design was carried out on people over 14 years old, selected from a probabilistic sample of households. A finger prick sample was tested by ELISA to detect IgG-class antibodies against SARS-C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
53
0
4

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 37 publications
(58 citation statements)
references
References 14 publications
1
53
0
4
Order By: Relevance
“…The same proportion of studies validated their methods internally to report accuracy (16,21,23,24,30,32,(34)(35)(36)(37)(38)(39)45,50,52) or used sensitivity and specificity given by manufacturers or other external studies (18)(19)(20)22,36,(40)(41)(42)(44)(45)(46)(47)(48)(49)(50)(51). We also noticed that it is quite unclear if the field teams followed standardized protocols for the data collection and testing.…”
Section: Discussionmentioning
confidence: 99%
“…The same proportion of studies validated their methods internally to report accuracy (16,21,23,24,30,32,(34)(35)(36)(37)(38)(39)45,50,52) or used sensitivity and specificity given by manufacturers or other external studies (18)(19)(20)22,36,(40)(41)(42)(44)(45)(46)(47)(48)(49)(50)(51). We also noticed that it is quite unclear if the field teams followed standardized protocols for the data collection and testing.…”
Section: Discussionmentioning
confidence: 99%
“…The City of Buenos Aires, adopted a "test and trace" policy. This program was carried out more strongly in poor neighborhoods, which have a younger population [12]. Mandatory hospitalization was also established for infants, still asymptomatic [6] [13].…”
Section: Discussionmentioning
confidence: 99%
“…Serological studies in different regions in England, Rio de Janeiro, Brazil, Tokyo, Japan, as well as Heinsberg, Germany estimate that SARS-CoV-2 seroprevalence is highest in adults aged under 35y ( 5 – 8 ). A serological study in a slum community in Buenos Aires, Argentina found the highest seroprevalence to be in adolescents aged 14-19y ( 25 ). In Belgium, persons aged 20-30 years had the highest estimated seroprevalence in persons aged below 80 ( 24 ) (with the oldest individuals likely affected by outbreaks in long-term care facilities).…”
Section: Age Variation In Seroprevalencementioning
confidence: 99%